O que o fantasma de Carmen Miranda está fazendo na Estação Espacial Três? representações, significações e ambigüidades nas "aparições" de Carmen Miranda nos EUA - Jesus, Sonia Melo de (2009)
Based on Homi K. Bhabha s (2003) premise that culture is located in the "in-betweenness" a hybrid space where the boundaries of gender, race, class, etc are negotiated this research aims to examine the various representations, meanings, and ambiguities of Carmen Miranda s "apparitions" in the USA. The central hypothesis of this work is that Carmen Miranda is a culturally hybrid figure, a border crosser, and an open text, therefore rich in significance. The representations, parodies, and impersonations of the artist in theatre, cinema, television, cartoons and science-fiction short stories are analyzed in the light of various theories regarding both the production and the consumption of stars in the U.S. American cultural industry, latinidad and hybridism. Alongside these theoretic approaches, this dissertation will also focus on the trickster figure, gender roles and stereotypes, among others. Thus, this dissertation seeks to emphasize the richness of interpretations generated from cultural differences, which are constantly being negotiated and renegotiated in the "in-betweeness" of cultural production.